Intramolecular Biradical Recombination of Dicarboxylic Acids to Unsaturated Compounds: A New Approach to an Old Kolbe Reaction - Meyers, Jérôme; Kurig, Nils; Gohlke, Clara; Valeske, Moritz; Panitz, Sinan; Holzhäuser, F. Joschka; Palkovits, Regina (ChemElectroChem, 2020)
The Kolbe or Non‐Kolbe electrolysis is one of the most studied electro‐organic reactions and a fundamental pillar of organic chemistry. In contrast to classical Kolbe dimerization of monocarboxylic acids, dicarboxylic acids are only scarcely subject for Kolbe electrolysis in the literature despite their vast natural abundance. Herein, we report on the intramolecular biradical recombination of dicarboxylic acids as a green way to prepare alkenes or alkynes over a newly proposed mechanistic route. Proceeding over a radical mechanism without dimerization, it clearly stands out from classical (Non‐)Kolbe electrolysis. In the presence of non‐toxic aqueous solvents, the desired products form in excellent yields (up to 83 %), which are the highest reported for this substrate class. Once feasibility had been shown for the electrolysis of methylsuccinic acid, we could demonstrate its application to a broad scope of different dicarboxylic acids. Biradical mechanism: A new approach to one of the most powerful electro‐organic reactions, showing an alternative pathway between the established Kolbe and Non‐Kolbe electrolysis routes, is reported. We focus on the intramolecular biradical recombination of dicarboxylic acids as a green way to prepare alkenes or alkynes.